Waste Utilization Potential of Oil Palm Industry in North Kalimantan Province, Indonesia - UTOMO, Mohamad Nur; MUBARAK, Ahmad; PRATIWI, Sulistya Rini; NAJMUDIN, Najmudin (Journal of Environmental Management and Tourism, 2023)
This research is aimed to identify the potential economic value of oil palm waste utilization and to construct an environmentally friendly business model based on oil palm waste utilization for the context of North Kalimantan Province. Method of research is descriptive using both quantitative and qualitative specifications. The results of research showed that plantation enterprises and farmers do not yet optimally utilize and manage oil palm waste into economically valuable products. The population around oil palm plantation perceive that oil palm waste from oil palm enterprises is safe and never bringing negative impact on environment. Economical value potential from oil palm waste utilization has been calculated and the number is positive and profitable. Other result indicated that the construction of a business model regarding oil palm waste management involves a collaboration between plantation enterprises, farmers and Village Enterprise (Bumdes-Badan Usaha Milik Desa) as the representative of community around the plantation. The expectation is that the utilization of oil palm waste will improve the welfare of farmers and community members, protect the environment and prevent social conflict concerning waste from happening.